Petersen-Varchenko’s Identity for Stirling Numbers of the First Kind - León-Vega, C. G.; López-Bonilla, J.; Agustín, S. Yáñez-San (Journal of the Institute of Engineering, 2018)
Stirling numbers of the first kind has some interesting interpretations. In this short paper, we exhibit an elementary deduction of an identity for Sn(m) obtained by Petersen-Varchenko.